Study of Zinc Oxide Nanoflower for Photocatalytic Applications Prepared via Hydrothermal Method - Vijayan, Nyaanalechumi; Ahmad, Mohd Khairul; Maarof , Nurul Amiera Shahida; Abdul Rahman, Nurul Huda (Evolution in Electrical and Electronic Engineering, 2021)
Zinc Oxide (ZnO) nanoflower have been commonly studied due to its tremendous application as photocatalysts in wastewater treatment. ZnO nanoflowers contributes great properties that are low cost, high redox potential. ZnO nanoflowers were synthesized using low temperature hydrothermal method of zinc acetate dihydrate which were used as zinc oxide precursor with hexamethylenetetramine (HMTA). Different concentration of nutrient was used to perform using the hydrothermal process. To characterize the phase and crystallinity of ZnO nanoflower were studied by X-ray diffraction (XRD). These experiments implement to investigated that flower-like shape ZnO with different morphology studied by Field Emission Scanning Electron Microscopy (FESEM). The photocatalytic performance of methylene Blue (MB) for different morphology flower-like ZnO was studied.